ANALYSIS OF LAND USE/LAND COVER VARIATION IN OKIGWE AREA, IMO STATE FROM 2000 TO 2020 USING GIS TECHNIQUES - Emetumah, Faisal; Iro, Sylvanus I.; Duru, Patricia N.; Chikezie, Prisca (African Journal of Social and Behavioural Sciences, 2023)
Population growth and urbanisation implies that the earth surface continues to change in different forms. The study analysed land use/ land cover (LU/LC) variation in Okigwe local government area (LGA), Imo State, using Geographic Information System (GIS) and remote sensing techniques, to determine the extent of changes in forest, urban development, water body, grass land and agricultural land, from 2000 to 2020. Data collection for the study involved Landsat images collected over the same year period with five years interval. These imageries were processed using the image classification of LU/LC of the study area. The results show that there is steady decrease in vegetation, agriculture, and grassland from years 2000 to 2020. Study results for the year 2000 showed that forest, agricultural land, and grass land classes were 35%, 31% and 4%, respectively while urban area was 19% of land within the study area. In the year 2020, it was observed that forest, agricultural land, and grass land were reduced to 30%, 28% and 2%, respectively while urban area increased to 29%. Based on the study findings, reduction in all the classes within the two decades studied were because of urbanisation. Therefore, Okigwe LGA should be well-planned with respect to land use, in order to check urban sprawl.